Comprehensive framework for internet banking adoption: an empirical analysis in the Indian context. (1st January 2014) - Vatnani, Rinku; Verma, Sanjeev
The study presents an integrated framework to analyse factors influencing consumer's acceptance of online banking services and tests its validity in the Indian context. The framework draws from two basic models most widely used in literature namely the technology acceptance model (TAM) and the technology readiness (TR) model. The results validate the basic TAM hypothesis that the intention to use internet banking is predicted by the two factors of perceived usefulness and perceived ease of using online banking technology. Age, gender and TR profiles moderate the relationship between the two factors and the behavioural intention to use internet banking. Trust in the bank was found to be another key factor driving a customer's intention. Knowledge of the customer demographics and TR profiles and how they influence his acceptance of internet banking can enable banks to understand their customers better and design tailor made marketing efforts towards activation.